IMPROVING INCENTIVES FOR THE PRODUCTION AND USE OF RENEWABLE ENERGY BY IMPOSING A LAND TAX ON LEGAL ENTITIES - Sirojetdinov Shokhrukhbek , Bokijonovich (THE INNOVATION ECONOMY, 2025)
This article examines the potential of using land tax for legal entities to promote renewable energy (RE) production and use in Uzbekistan. The study analyzes tax incentives, the economic efficiency of RE projects, and infrastructure constraints. A mixed-methods approach was employed, combining qualitative analysis (of legislation and enterprise documents) and quantitative analysis (of RE statistics for 2020–2024). Findings show that land tax incentives have increased RE investments, but legislative ambiguities, skill shortages, and financial barriers persist. Recommendations tailored to Uzbekistan’s context are provided.